Continuous response fluorescence sensor for three small molecules based on nitrogen-doped carbon quantum dots from prunus lannesiana and their logic gate operation - Guo, Zicheng; Liu, Xuerui; Yu, Haiyu; Hou, Faju; Gao, Shanmin; Zhong, Linlin; Xu, Hui; Yu, Yang; Meng, Junli; Wang, Ruru (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2021)
Synthesis of N-CQDs and its sensing mechanism for Fe3+, AA and H2O2. [Display omitted] •A simple “on-off-on-off” continuous response fluorescence sensor was developed.•The analytical process is fast, and the three inputs “Logic gate” is achieved. In this study, an environmentally friendly and water-soluble nitrogen-doped carbon quantum dots (N-CQDs) with quantum yield (QY) of 8.59% were prepared by one-step hydrothermal synthesis without any chemical reagent using the leaves of prunus lannesiana as precursors. The properties and quality of N-CQDs were investigated by Ultraviolet–visible absorption spectroscopy, infrared spectroscopy, X-ray photoelectron spectroscopy, zeta potential, high-resolution transmission electron microscopy and fluorescence spectroscopy. The fluorescence of the prepared N-CQDs can be quenched by Fe3+ through the synergistic effect of the formation of non-fluorescent complex and internal filtration effect (IFE) between Fe3+ and N-CQDs. And the quenched fluorescence can be “turned on” after adding ascorbic acid (AA) because Fe3+ can be released from the surface of N-CQDs through the redox reaction between AA and Fe3+. While the restored fluorescence can be “turned off” again by hydrogen peroxide (H2O2) due to the re-oxidation of Fe2+ to Fe3+. So, the three inputs “logic gate” is achieved and the “on-off-on-off” continuous response fluorescence sensor is formed, which can be applied for the continuous detection of Fe3+, AA and H2O2 with the linear range of 40–260 μM, 10–200 μM and 40–140 μM, respectively. Finally, the sensor was successfully applied to determine Fe3+, AA and H2O2 in real samples with the satisfactory recoveries (95.35%-104.10%) and repeatability (relative standard deviation (RSD) ≤ 1.68%). The continuous response fluorescence sensor prepared by simple green synthesis route has the characteristics of fast response, acceptable sensitivity and good selectivity.